The Iraq Effect The Middle East After the Iraq War - Wehrey, Frederic (RAND Corporation, 2010)
Regardless of its outcome, the Iraq War has had a transformative effect on the Middle East. To equip U.S. policymakers to better manage the war's long-term consequences, the authors analyzed its effects on the regional balance of power, local perceptions of U.S. credibility, the domestic stability of neighboring states, and trends in terrorism after conducting extensive interviews in the region and drawing from an array of local media sources.